Pengaruh Trend Busana Muslim Melalui Penggunaan Instagram Terhadap Perilaku Konsumtif Gen-Z - Maisara (Jurnal Ekonomi dan Bisnis Digital, 2024)
Consumptive behavior is excessive buying behavior by prioritizing secondary and tertiary needs over primary needs which causes a person to become wasteful. In the current conditions, lifestyle and appearance are important among Gen Z, often what they do is not a major need, but only to fulfill desires and pursue prestige. By prioritizing appearance, Gen Z has a habit of buying items or what is often called shopping. Excessive shopping is usually referred to as consumptive behavior. This research aims to determine whether there is an influence of Muslim fashion trends, the use of Instagram, on the consumptive behavior of Gen Z, Bogor Regency. This research method uses a quantitative approach with the Structural Equation Modeling-Partial Least Square (SEM-PLS) method which is collected through questionnaires. The sample for this research was 100 respondents with a collection technique using purposive sampling and assisted by using Partial Least Square Structural Equation Modeling (PLS) analysis. The results of this research show that the Muslim Fashion Trend has a positive and significant influence on consumption, the path coefficient results show a value of 0.849, which is above 0, then the results of the hypothesis test show a statistical t value of 26,580> 1.96 and a p-value of 0.000 < 0.05 so hypothesis accepted. Instagram use has a negative and insignificant effect on consumer behavior. shows that the use of Instagram social media does not have a significant and negative effect on consumption, the path coefficient results show a value of 0.017, which is above 0, then the results of the hypothesis test show a statistical t value of 0.257 < 1.96 and a p-value of 0.797> 0.005. This result has meaning that this shows that the use of Instagram has not been maximized in creating feelings of interest among Gen Z consumers in the city of Bogor.